5/9 + 5/11 - 5/13
7/9 + 7/11 - 7/13
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{1}{3}-\frac{3}{5}+\frac{5}{7}-\frac{7}{9}+\frac{9}{11}-\frac{11}{13}+\frac{13}{15}+\frac{11}{13}-\frac{9}{11}+\frac{7}{9}-\frac{5}{7}+\frac{3}{5}\)
\(=\left(-\frac{3}{5}+\frac{3}{5}\right)+\left(\frac{5}{7}-\frac{5}{7}\right)+\left(-\frac{7}{9}+\frac{7}{9}\right)+\left(\frac{9}{11}-\frac{9}{11}\right)+\left(-\frac{11}{13}+\frac{11}{13}\right)+\left(\frac{1}{3}+\frac{13}{15}\right)\)
\(=\frac{1}{3}+\frac{13}{15}\)
\(=\frac{6}{5}\)
ta có \(\frac{\frac{4}{5}-\frac{4}{11}+\frac{4}{13}}{\frac{9}{5}-\frac{9}{11}+\frac{9}{13}}+\frac{\frac{5}{7}+\frac{5}{11}-\frac{5}{13}}{\frac{9}{7}+\frac{9}{11}-\frac{9}{13}}\)
\(=\frac{4\left(\frac{1}{5}-\frac{1}{11}+\frac{1}{13}\right)}{9\left(\frac{1}{5}-\frac{1}{11}+\frac{1}{13}\right)}+\frac{5\left(\frac{1}{7}+\frac{1}{11}-\frac{1}{13}\right)}{9\left(\frac{1}{7}+\frac{1}{11}-\frac{1}{13}\right)}\)
\(=\frac{4}{9}+\frac{5}{9}=\frac{9}{9}=1\)
\(A=\dfrac{1}{3}-\dfrac{3}{5}+\dfrac{5}{7}+\dfrac{7}{9}+\dfrac{9}{11}-\dfrac{11}{13}+\dfrac{13}{15}-\dfrac{9}{11}-\dfrac{7}{9}-\dfrac{5}{7}+\dfrac{3}{5}-\dfrac{1}{3}\left(+\dfrac{7}{9}\rightarrow-\dfrac{7}{9}\right)\)
\(\Rightarrow A=\dfrac{1}{3}-\dfrac{1}{3}-\dfrac{3}{5}+\dfrac{3}{5}+\dfrac{5}{7}-\dfrac{5}{7}+\dfrac{7}{9}-\dfrac{7}{9}+\dfrac{9}{11}-\dfrac{9}{11}-\dfrac{11}{13}+\dfrac{13}{15}\)
\(\Rightarrow A=-\dfrac{11}{13}+\dfrac{13}{15}\)
\(\Rightarrow A=\dfrac{-11.15+13.13}{13.15}\)
\(\Rightarrow A=\dfrac{-165+169}{195}=\dfrac{4}{195}\)
a, \(\dfrac{5}{9}.\dfrac{10}{11}+\dfrac{5}{9}.\dfrac{14}{11}-\dfrac{5}{9}.\dfrac{15}{11}=\dfrac{5}{9}.\left(\dfrac{10}{11}+\dfrac{14}{11}-\dfrac{15}{11}\right)=\dfrac{5}{9}.\dfrac{9}{11}=\dfrac{5}{11}\)
b, \(\dfrac{6}{7}.\dfrac{8}{13}+\dfrac{6}{13}.\dfrac{9}{7}-\dfrac{3}{13}.\dfrac{6}{7}\)\(=\dfrac{6}{7}.\left(\dfrac{8}{13}-\dfrac{3}{13}\right)+\dfrac{6}{13}.\dfrac{9}{7}=\dfrac{6}{7}.\dfrac{5}{13}+\dfrac{54}{91}=\dfrac{30}{91}+\dfrac{54}{91}=\dfrac{84}{91}=\dfrac{12}{13}\)
Bạn ơi, gõ latex cho dễ nhìn nhé!
\(\dfrac{1}{3}-\dfrac{3}{5}+\dfrac{5}{7}-\dfrac{7}{9}+\dfrac{9}{11}-\dfrac{11}{13}+\dfrac{13}{15}+\dfrac{11}{13}-\dfrac{9}{11}+\dfrac{7}{9}-\dfrac{5}{7}+\dfrac{3}{5}-\dfrac{1}{3}\)
\(=\left(\dfrac{1}{3}-\dfrac{1}{3}\right)-\left(\dfrac{3}{5}-\dfrac{3}{5}\right)+\left(\dfrac{5}{7}-\dfrac{5}{7}\right)-\left(\dfrac{7}{9}-\dfrac{7}{9}\right)+\left(\dfrac{9}{11}-\dfrac{9}{11}\right)-\left(\dfrac{11}{13}-\dfrac{11}{13}\right)+\dfrac{13}{15}\)
\(=\dfrac{13}{15}\)
31−53+75−97+119−1311+1513+1311−119+97−75+53−31
=(13−13)−(35−35)+(57−57)−(79−79)+(911−911)−(1113−1113)+1315=(31−31)−(53−53)+(75−75)−(97−97)+(119−119)−(1311−1311)+1513
=1315=1513
\(\frac{\frac{5}{9}+\frac{5}{11}-\frac{5}{13}}{\frac{7}{9}+\frac{7}{11}-\frac{7}{13}}=\frac{5\left(\frac{1}{9}+\frac{1}{11}-\frac{1}{13}\right)}{7\left(\frac{1}{9}+\frac{1}{11}-\frac{1}{13}\right)}=\frac{5}{7}\)